Heat Stress-Induced Dysbiosis of Porcine Colon Microbiota Plays a Role in Intestinal Damage: A Fecal Microbiota Profile - Hu, Canying; Patil, Yadnyavalkya; Gong, Dongliang; Yu, Tianyue; Li, Junyu; Wu, Lianyun; Liu, Xiaoxi; Yu, Zhichao; Ma, Xinbing; Yong, Yanhong; Chen, Jinjun; Gooneratne, Ravi; et al. (Frontiers in Veterinary Science, 2022)
The pathological mechanisms of gastrointestinal disorders, including inflammatory bowel disease (IBD), in pigs are poorly understood. We report the induction of intestinal inflammation in heat stressed (HS) pigs, fecal microbiota transplantation from pigs to mice, and explain the role of microorganisms in IBD. Twelve adult pigs were subjected to HS (34 ± 1 °C; 75–85% relative humidity) and 12 control pigs (CP) were kept at 25 ± 3 °C and the same humidity. Pigs were sacrificed on days 1, 7, 14, 21. Colonic content microbiome analyses were conducted. Pseudo-germ-free mice were fed by gavage with fecal microbiota from HS-pigs and CP to induce pig-like responses in mice. From 7 d, HS-pigs exhibited fever and diarrhea, and significantly lower colonic villus length, crypt depth/width, and goblet cell number. Compared with each control group, the concentration of cortisol in the peripheral blood of HS pigs gradually increased, significantly so on days 7, 14, and 21 (P < 0.01). While the concentration of endotoxin in HS pigs’ peripheral blood was significantly higher on days 7, 14 (P < 0.01), and 21 (P < 0.05) compared with that of the control group. The colonic microflora composition of HS-pigs was different to that of CP. By day 14, opportunistic pathogens (e.g., Campylobacterales) had increased in HS-pigs. The composition of the colonic microflora in mice administered feces from HS-pigs was different from those receiving CP feces. Bacteroides were significantly diminished, Akkermansia were significantly increased, and intestinal damage and goblet cell numbers were higher in mice that received HS-pig feces. Moreover, we verified the relevance of differences in the microbiota of the colon among treatments. Heat stress promotes changes in gut microflora composition, which can affect the colonic microbial structure of mice through fecal microbiota transplantation; the molecular mechanisms require further investigation. This study enhanced our understanding of stress-induced IBD and the increase in diarrhea in mammals subjected to prolonged HS. Our results provide useful information for preventing or ameliorating deficits in pig production caused by prolonged exposure to high temperatures.